Identifying Competency Gaps to Inform Professional Development for Pancasila Education Teachers - Rahma Tri Wulandari; Pedro Jurado de los Santos; Antonio Navio Gamez (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
A mismatch between expected and actual teacher competencies in curriculum implementation highlights the need for evidence-based professional development (PD), yet empirical studies examining professional and pedagogical competency gaps among Pancasila Education teachers within MGMP communities remain limited. This study examines the discrepancy between ideal competencies, based on national teacher competency standards (Ministerial Regulation No. 16/2007), and teachers' perceived actual competencies to inform needs-based PD design. Using a descriptive cross-sectional survey design, data were collected from 30 teachers selected through purposive sampling based on active teaching status and MGMP membership. A structured questionnaire was administered, and the data were analysed using gap analysis as a diagnostic tool for identifying PD needs. Results showed that the average gap in pedagogical competence (0.77) slightly exceeded that of professional competence (0.73). The largest gaps were found in civic knowledge content, contextual content selection, deep learning design, and assessment indicator development, whereas ICT use showed the smallest gap (0.60). These findings contribute to the literature on needs-based professional development by identifying priority competency areas that can inform targeted, evidence-based PD planning within teacher professional communities.